2022
DOI: 10.1001/jamanetworkopen.2022.29282
|View full text |Cite
|
Sign up to set email alerts
|

Global Frequency and Clinical Features of Stroke in Patients With Tuberculous Meningitis

Abstract: IMPORTANCE Stroke in tuberculous meningitis (TBM) is associated with significant morbidity and mortality.OBJECTIVE To determine the country-specific, regional, and overall prevalence of stroke among patients with TBM, including their clinical manifestations, stroke locations, and outcomes.EVIDENCE REVIEW This systematic review searched records in MEDLINE by PubMed, Scopus, and EMBASE until July 2020 for relevant articles on the occurrence and characteristics of stroke in TBM.Randomized clinical trials and coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 77 publications
0
22
0
2
Order By: Relevance
“…A systematic review showed that the global frequency of stroke in TBM is approximately 30%, meaning that 3 out of 10 patients with TBM will eventually develop a stroke. 6,7 The pathophysiologic mechanism responsible for cerebral infarction includes obliterative vasculitis, intimal proliferation and hypercoagulable state. 3 Among the involved vascular territories, the most affected by TB are those from the anterior circulation specifically the lateral striate artery, the medial striate artery and the middle cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review showed that the global frequency of stroke in TBM is approximately 30%, meaning that 3 out of 10 patients with TBM will eventually develop a stroke. 6,7 The pathophysiologic mechanism responsible for cerebral infarction includes obliterative vasculitis, intimal proliferation and hypercoagulable state. 3 Among the involved vascular territories, the most affected by TB are those from the anterior circulation specifically the lateral striate artery, the medial striate artery and the middle cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to the brain region usually affected by stroke, specifically the basal ganglia and the internal capsule. 6,8 Sy et al 6 found that the frequency of poor outcomes among patients with TBM experiencing stroke was 51%, with a mortality rate of 21%. Thus, early initiation of appropriate therapy is crucial to improve prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advanced stage of tuberculosis disease, basal and sylvian localization and visual impairment are among the predictive factors for the occurrence of stroke having been reported [5]. It is the cause of high morbidity and mortality with a life-threatening prognosis [14,15]. The functional prognosis will depend on the occurrence of neurological sequelae.…”
Section: Evolution -Prognosismentioning
confidence: 99%
“…Manifestasi klinis yang dirasakan oleh pasien dengan meningitis TB kebanyakan melibatkan sistem saraf pusat, sehinga akan mengalami sakit kepala secara terus menerus, demam, leher terasa kaku, batuk perkepanjangan, mual dan muntah. Dari sisi psikologis emosional juga menjadi cepat berubah yaitu gampang marah dan bingung, mengantuk, hingga pingsan (Sy et al, 2022).…”
Section: Pendahuluanunclassified